Evaluation of toxicological and teratogenic effects of carbosilane glucose glycodendrimers in zebrafish embryos and model rodent cell lines - Liegertová, Michaela; Wrobel, Dominika; Herma, Regina; Müllerová, Monika; Šťastná, Lucie Červenková; Cuřínová, Petra; Strašák, Tomáš; Malý, Marek; Čermák, Jan; Smejkal, Jiří; Štofik, Marcel; Maly, Jan (Nanotoxicology, 2018)
Glycodendrimers (Glyco-DDMs) represent a rapidly growing class of nanoparticles with promising properties for biomedical applications but concerns regarding the impact on human health and environment are still justified. Here we report, for the first time, the comparative study of in vivo developmental toxicity of carbosilane Glyco-DDMs and their cytotoxicity in vitro. Carbosilane Glyco-DDMs (generation 1-3) containing 4, 8, and 16 β-d-glucopyranosyl units at the periphery (DDM1Glu, DDM2Glu, and DDM3Glu) were synthesized and characterized by 1H, 13C and 29Si NMR, mass spectrometry, dynamic light scattering, atomic force microscopy (AFM), and computer modeling. In vitro cytotoxicity assay (MTT) of DDM1-3Glu was performed on three different rodent cell lines (Cricetulus griseus) - B14 (ATCC, CCL-14.1), BRL 3A (ATCC, CRL-1442), and NRK 52E (ATCC, CRL-1571). Overall, very low cytotoxicity was observed with calculated IC50 in mM range with slight difference between each cell line and DDM generation investigated. Modified fish embryo test (FET) was further used for DDM3Glu developmental toxicity testing on zebrafish (Danio rerio) embryos. While seemingly harmless to intact embryos, adverse effects of DDMs on the embryonic development become evident after chorion removal (LD50=2.78 µM at 96 hpe). We summarized that the modified FET test showed a two to three orders of magnitude difference between the in vitro cytotoxicity and in vivo developmental toxicity of DDM3Glu. While, in general, the Glyco-DDMs show great promises as efficient vectors in targeted drug delivery or as therapeutic molecules itself, we suggest that their developmental toxicity should be thoroughly investigated to exclude safety risks associated with their potential biomedical use.
Keywords: Embryonic Development; Cell Line; Glucose; glukosa; embryo nesavčí; Models, Molecular; testy toxicity; teratogeny; Embryo, Nonmammalian; povrchové vlastnosti; teratogenicity; toxicity; glycodendrimers; zebrafish; Dendrimers; Carbosilane dendrimers; dendrimery; Surface Properties; molekulární modely; molecular modeling; zvířata; Humans; Zebrafish; dánio pruhované; Silanes; Cricetulus; Lethal Dose 50; viabilita buněk; Cell Survival; embryonální vývoj; buněčné linie; silany; LD50; Toxicity Tests; Teratogens; lidé; Animals